Misyār Marriage In The View Of Yusuf Qardawi And Abdullah Muhammad Ath-Thayyar: Challenges And Constructive Approaches - Nur, Muhammad Yaumil Awal; Rusdaya Basri; Muhiddin Bakri; Islamul Haq; Fikri; Abdul Karim bin Khairuddin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
This research focuses on the discussion of misyār marriage as one of the contemporary phenomena that did not exist in the time of the Prophet Muhammad SAW by using a type of literature research with a qualitative approach and analyzing existing data inductively. The results of the study show that misyār marriage was triggered by its emergence due to the massive development of the times. One of the indicators is the emergence of women who no longer live at home and work, so that they are economically independent. In addition, the varied work of men keeps them away from their wives which then causes problems. By analyzing the opinions of several scholars who have detailed the marriage of misyār, such as Yusuf Qardhawi and Abdullah Muhammad Aṭ-Ṭayyar, it can be concluded that this opinion cannot be separated from the concept of legal change of Ibn Qayyim which is also influenced by the changing times. This study proposes to deepen the understanding of the concept of nikah misyār to answer the development of the times and its relevance to Islamic teachings, namely ṣaliḥ likulli az-zamān wa al-makān. In addition, this study also offers constructive approaches in assessing the validity of misyār marriage. This research is expected to enrich the discourse around marriage in Islam and become a medium for the wider community to know this phenomenon.